The Relationship of Behavior and Environment to the Incidence of Malaria in the Work Area of Oesao Public Health Center (PHC) of East Kupang Sub-District of Kupang District in 2013 - Titik Yuliati; Yayi S Prabandari; Tri Baskoro T Satoto (Pusat Kedokteran Tropis, 2013)
ABSTRACT Introduction: Oesao PHC is one of three PHCs in Kupang District experiencing increased malaria cases. According to API figure, its rate in 2008 was 7.01% and in 2009 it decreased to 4.04%; however, the rate showed an increase again in 2010 up to 7. 67%o (Kupang District Health Office, 2010).The work area of Oesao PHC has a heterogeneous society with high malaria cases in each year; it is because the residents have habits to sleep without using nets, people perform activities at night without the use of mosquito repellent, there is an availability of mosquito breeding place and resting place and there is a lack of compliance in taking medication.Objectives: To analyze the relationship between behavior and the environment and the incidence of malaria.Methods: This was an observational analytic study with a case-control study design2. The samples in this study were part of the populations residing within the work area of Oesao PHC of East Kupang Sub-District of Kupang District. The sample size was 116 people3 selected using a random and matching method. Data were analyzed by chi-square test for calculating the value of OR (odds ratio) to determine the magnitude of the risk2 .Results: There was a significant association between the use of nets (OR = 0.061 with p = 0.000, p < 0.05), the use of mosquito repellent or anti-mosquito drugs (OR = 3.417 and p = 0.003, p < 0.05), the use of wire gauze on ventilation (OR = 7.187 with p = 0.000, p < 0.05), the condition of home walls (OR = 2.318 with p = 0.041, p < 0.05), the availability of ceiling OR = 2.657 with p = 0.000, p<0.05), the presence of cattle sheds (OR = 4.742 with p = 0.001, p <0,05), the presence of puddle around the home (OR = 2.007 and p = 0.047, p < 0.05), and the presence of shrubs around the home (OR = 2.706 with p = 0.000, p < 0.05) and the incidence of malaria in Oesao PHC.Conclusion: The incidence of malaria in the work area of Oesao PHC was related to behavior and physical environment inside and outside the house.Keywords: behavior, environment, malaria